The influence of labelling on symbolic understanding and dual representation in autism spectrum condition. (June 2020) - Wainwright, Bethany R; Allen, Melissa L; Cain, Kate
Abstract: Background and aims: Children with autism spectrum condition often have specific difficulties understanding that pictorial symbols refer to real-world objects in the environment. We investigated the influence of labelling on the symbolic understanding and dual representation of children with autism spectrum condition. Methods: Children with autism spectrum condition and typically developing children were shown four coloured photographs of objects that had different functions across four separate trials. The participants were given either a novel label alongside a description of the object's function or a description of the object's function without a label. Children were then given 30 seconds to interact with an array of stimuli (pictures and objects) in a mapping test and in a generalisation test for each trial. This exploration phase allowed for spontaneous word–picture–referent mapping through free-play, providing an implicit measure of symbolic understanding. Results: We found no significant difference in word–picture–referent mapping between groups and conditions. Both groups more often performed the described action on the target object in the exploration phase regardless of condition. Conclusions and implications: Our results suggest that a spontaneous measure of symbolic understanding (such as free-play) may reveal competencies in word–picture–referent mapping in autism spectrum condition.